Batalhas sem heróis: as metamorfoses do punk na sociedade brasileira contemporânea - Guerra, Paula (2021)
This article focuses on the metamorphosis that punk, as an artistic and cultural form, movement, (sub) (post) culture and scene, has undergone over time. This analysis has as its central context Brazil and the Global South. Thus, we start by conducting four semistructured interviews, to account for the modes of action and representation of social actors as a basic element for the construction of a scientific problem around the importance of the punk movement today, as a political weapon and form of resistance and existence. Thus, we focus on four key themes, namely the relationship between punk and black feminism, Afro-indigenous punk, LGBTQI+ punk and peripheral punk. The memory of a troubled political, social and economic past is the framework of these metamorphoses, as well as it will be our starting point, so that we can understand the discourses, the senses and the meanings of punk in contemporary Brazilian society